Functional response of U.S. grasslands to the early 21st‐century drought. Issue 8 (1st August 2014) - Moran, M. Susan; Ponce-Campos, Guillermo E.; Huete, Alfredo; M Claran, Mitchel P.; Zhang, Yongguang; Hamerlynck, Erik P.; Augustine, David J.; Gunter, Stacey A.; Kitchen, Stanley G.; Peters, Debra P. C.; Starks, Patrick J.; Hernandez, Mariano
Abstract : Grasslands across the United States play a key role in regional livelihood and national food security. Yet, it is still unclear how this important resource will respond to the prolonged warm droughts and more intense rainfall events predicted with climate change. The early 21st‐century drought in the southwestern United States resulted in hydroclimatic conditions that are similar to those expected with future climate change. We investigated the impact of the early 21st‐century drought on aboveground net primary production (ANPP) of six desert and plains grasslands dominated by C4 (warm season) grasses in terms of significant deviations between observed and expected ANPP. In desert grasslands, drought‐induced grass mortality led to shifts in the functional response to annual total precipitation ( P T ), and in some cases, new species assemblages occurred that included invasive species. In contrast, the ANPP in plains grasslands exhibited a strong linear function of the current‐year P T and the previous‐year ANPP, despite prolonged warm drought. We used these results to disentangle the impacts of interannual total precipitation, intra‐annual precipitation patterns, and grassland abundance on ANPP, and thus generalize the functional response of C4 grasslands to predicted climate change. This will allow managers to plan for predictable shifts in resources associated with climate change related to fire risk, loss of forage, and ecosystem services.